The Development of Optomechanical Sensors—Integrating Diffractive Optical Structures for Enhanced Sensitivity - Faolan Radford McGovern; Aleksandra Hernik; Catherine Grogan; George Amarandei; Izabela Naydenova (Sensors, 2023)
The term optomechanical sensors describes devices based on coupling the optical and mechanical sensing principles. The presence of a target analyte leads to a mechanical change, which, in turn, determines an alteration in the light propagation. Having higher sensitivity in comparison with the individual technologies upon which they are based, the optomechanical devices are used in biosensing, humidity, temperature, and gases detection. This perspective focuses on a particular class, namely on devices based on diffractive optical structures (DOS). Many configurations have been developed, including cantilever- and MEMS-type devices, fiber Bragg grating sensors, and cavity optomechanical sensing devices. These state-of-the-art sensors operate on the principle of a mechanical transducer coupled with a diffractive element resulting in a variation in the intensity or wavelength of the diffracted light in the presence of the target analyte. Therefore, as DOS can further enhance the sensitivity and selectivity, we present the individual mechanical and optical transducing methods and demonstrate how the DOS introduction can lead to an enhanced sensitivity and selectivity. Their (low-) cost manufacturing and their integration in new sensing platforms with great adaptability across many sensing areas are discussed, being foreseen that their implementation on wider application areas will further increase.